The Global Catholic Missionary Societies and the Spread of Marian Devotion in Pre-Twentieth-Century Vietnam - Bien, Duong Van (Brill, 2024)
Abstract Dating back many years, Marian devotion is currently a ubiquitous phenomenon among Vietnamese Catholics in Vietnam. This article examines the endeavours of specific global Catholic missionary societies – the Society of Jesus (S.J.), the Dominican Order or the Order of Preachers (O.P.) and the Society of Foreign Missions of Paris (mep) – in spreading Marian devotion in pre-twentieth-century Vietnam. In doing so, the article seeks to demonstrate that the prevalence of Marian devotion primarily resulted from the enduring efforts of global Catholic missionaries during the stages of proselytization. This argument aims to challenge the prevailing notion that the primordial Vietnamese cultural identity, widely known for emphasizing female status and Mother Goddess worship, exerted its influence on the elevation of Marian devotion among Vietnamese Catholics during the course of history.
Keywords: Dominican; Jesuit; Marian devotion; Vietnamese Catholicism; mep; missionary societies